The role of processes and contents in human memory: an item response theory approach - Ferreira, Aristides; Almeida, L.; Prieto, G. (Journal of Cognitive Psychology, 2011)
This study investigated the specificities and communalities of visuospatial and verbal memory contents, as well as short-term memory and working memory (STM and WM) processes with the use of Rasch models as an alternative to the previous studies based on the classical test theory. A sample of 547 undergraduate students executed four computerised tasks, each consisting of verbal-numeric WM, visuospatial WM, verbal-numeric STM, and visuospatial STM content. Confirmatory factor analyses indicated that visuospatial and verbal-numeric memory are distinct, but correlated variables. Findings also support a domain-general view of WM capacity distinct from domain-specific storage. With the use of Rasch models, our results confirm previous experimental, psychometric, and neuropsychological studies, highlighting that memory span tasks can be divided into separate subsystems for content and processes. This study also shows that better results are obtained when models with person parameter estimates (provided from Rasch models) are adopted, rather than summed raw scores.